Characterization of BRAF mutation in patients older than 45 years with well-differentiated thyroid carcinoma - Barreno,Luis Rene Quiroa (2022)
Abstract Introduction: Papillary thyroid carcinoma is the most frequent endocrine neoplasia and its incidence has tripled over the past 35years. Although papillary thyroid carcinoma carries a good prognosis, 10%–30% of patients still develop recurrence and metastasis. Some clinical and genetic features are associated with worse prognosis. The most frequent mutation is the BRAF p.V600E, which has been associated with many clinical features of poor prognosis. However, many studies have produced controversial results without any association between BRAF mutation and clinicopathological features of poor prognosis. Objective: Since the prognostic value of BRAF mutations remains controversial, this study aims to investigate the importance of this mutation in therapeutic decisions for papillary thyroid carcinoma. Methods: Therefore, we evaluated whether the presence of BRAF mutation is associated with features of poor prognosis in 85 patients with papillary thyroid carcinoma older than 45years treated at A.C. Camargo Cancer Center, from 1980 to 2007. BRAF mutation was evaluated by pyrosequencing. Statistical analysis was performed using SPSS. Results: The mean age of patients was 54 years (range: 45 - 77 years), 73 were women (85.8%) and 12 were men (14.2%). Among them, 39 cases (45.9%) presented extrathyroidal extension and 11 cases had recurrent disease. BRAF mutation was detected in 57 (67%) patients. No significant association was observed between BRAF mutation and gender (p =0.743), age (p = 0.236), N-stage (p =0.423), vascular and perineural infiltration (p =0.085 or multifocality (p = 1.0). Although not statistically significant, the majority of patients with recurrent disease were BRAF positive (9 out of 11) (p =0.325). Patients affected by BRAF mutation are associated with tumors larger than 1 cm (p =0.034) and with extrathyroidal extension (p =0.033). Conclusion: Although BRAF testing is widely available, there are no consistent data to support improvement in outcomes from incorporating it into therapeutic decision for thyroid cancer.